2019
DOI: 10.1038/s41427-019-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light photocatalysis by carbon-nano-onion-functionalized ZnO tetrapods: degradation of 2,4-dinitrophenol and a plant-model-based ecological assessment

Abstract: The visible-light-induced photocatalytic performance of a three-dimensional (3D) hybrid composite based on carbon nano-onion (CNO)-functionalized zinc-oxide tetrapods (T-ZnO) was investigated to study the photocatalytic degradation of 2,4-dinitrophenol (DNP). The hybrid CNO-functionalized T-ZnO 3D composite was successfully developed via a facile one-step process. The CNOs, synthesized via a green route from flaxseed oil, were decorated on the surface of T-ZnO via chemical mixing. Such a hybrid composite allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(50 citation statements)
references
References 61 publications
(82 reference statements)
0
47
0
Order By: Relevance
“…Jayswal and Moirangthem reported a k app value of 5:9 × 10 -3 min -1 for photocatalytic degradation of methyl orange after 150 min under visible light irradiation using an SnS/ZnO heterostructure as a photocatalyst [66]. In another study, Park et al reported a k app value of 2:7 × 10 -3 min -1 for photocatalytic degradation of 2,4-dinitrophenol after 140 min under visible light irradiation using functionalized zinc oxide tetrapods as photocatalysts [67]. Türkyilmaz et al reported a k app value of 7:5 × 10 -3 min -1 for visible light photocatalytic degradation of tartrazine after 150 min using Fe-doped ZnO as photocatalysts [22].…”
Section: Optical Studymentioning
confidence: 99%
“…Jayswal and Moirangthem reported a k app value of 5:9 × 10 -3 min -1 for photocatalytic degradation of methyl orange after 150 min under visible light irradiation using an SnS/ZnO heterostructure as a photocatalyst [66]. In another study, Park et al reported a k app value of 2:7 × 10 -3 min -1 for photocatalytic degradation of 2,4-dinitrophenol after 140 min under visible light irradiation using functionalized zinc oxide tetrapods as photocatalysts [67]. Türkyilmaz et al reported a k app value of 7:5 × 10 -3 min -1 for visible light photocatalytic degradation of tartrazine after 150 min using Fe-doped ZnO as photocatalysts [22].…”
Section: Optical Studymentioning
confidence: 99%
“…Conventional techniques [3], employed for the removal of water pollutants, suffer from several disadvantages like high cost, accumulation of toxic sludge, environmental pollution, and others. An alternative to these techniques is photocatalysis [4] using semiconductor nanomaterials (SNMs), which efficiently degrades organic wastes, such as dyes, drugs, etc. from aqueous media [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, carbon-based composite materials have emerged as potentially promising targets for growth of electroactive tissues such as cardiac muscle, nerve and bone since the stimulation of osteogenesis due to inherent piezoelectric features of bone tissues attainable on conductive scaffolds [5][6][7][8][9] . Among these, blended composites between nanostructured carbon materials (carbon nanofibers/nanotubes and graphene) and biocompatible polymers (poly(vinyl alcohol), alginate, poly(lactide-co-glycolide and collagen) have been widely investigated as future materials for tissue engineering [10][11][12][13][14][15][16][17] . However, it is often essential to use a substantial amount of nanostructured carbons as a major component for achieving high conductivity in the composites.…”
mentioning
confidence: 99%